What Should Research Study Practice Be in the AI Era? ——Also on Three Taboos and Three Priorities of Study Tour Education - Qiang Wang (Education Research on Study Tours and Practice, 2026)
In June 2026, an editorial in People’s Daily highlighted the urgent need to rectify the utilitarian tendency and return to the fundamental educational value of study tour practice. Taking the dual events of the editorial’s release and the research investigation in Heilongjiang Province as the research background, this paper systematically sorts out the core criteria for standardized development and the positive orientation for high-quality development of study tours. It further summarizes five bottom-line principles for the healthy development of the industry: clarifying educational orientation, ensuring safety and transparency, opposing anxiety-oriented marketing, promoting low-cost replicability, and improving the evaluation system. Guided by the concept of the Golden Seed special issue, this study explores the practical paths for study tour education to return to its nurturing essence, aiming to provide empirical references and decision-making support for the standardized and high-quality development of study tour practice in primary and secondary schools.